أثر الاشتراطات البيئية على تنافسية الصادرات السلعية دراسة قياسية لمجموعة من الدول النامية - هميسي, كوثر (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
الملخص: هدفت دراستنا هذه إلى معرفة مدى تأثير الاشتراطات او المعايير البيئية على تنافسية الصادرات السلعية وهذا من خلا ل دارستنا إلى ثلاثة عشر دولة نامية، للفترة (2004-2020). ومن أجل الإجابة عن الإشكالية الرئيسية تم بناء ثلاث نماذج قياسية، حيث يتعلق الأول بنموذج حصة الصادرات السلعية، والنموذج الثاني بمؤشر تركز الصادرات، والنموذج الثالث يتعلق بمؤشر تنوع الصادرات. وبناء على نتائج الاختبارات التي أجريت وهي اختبارات الإستقرارية والتجانس والتكامل المشترك تبين أن المتغيرات مستقرة عند الفرق الأول واختبارات التجانس أظهرت عدم التجانس في النماذج الثلاثة ،أما اختبار التكامل المشترك فبين عدم وجود علاقة طويلة بين المتغيرات المستقلة والمتغير التابع في النماذج الثلاثة، وعليه تم التقدير بطريقة المربعات الصغرى الوهمية (LSDV)وكانت النتائج بوجود علاقة سالبة بين الانبعاثات الكربونية وحصة الصادرات السلعية ومؤشري التركز والتنوع، وعلاقة إيجابية بين الناتج المحلي الإجمالي وحصة الصادرات ومؤشري التركز والتنوع ،ويوجد علاقة سالبة بين مؤشر حرية التجارة وحصة الصادرات ومؤشري التركز والتنوع كما يوجد علاقة موجبة بين مؤشر نضوب الموارد الطبيعية وحصة الصادرات السلعية وعلاقة سالبة بينها وبين مؤشر التركز والتنوع. Abstract: Our study amis to know the extent to which environmental requirements or standards affect the competitiveness of commodity exports and this is through our studies to thirteen developing countries for the period (2004-2020). In order to answer the main problem, three standard models were developed, the first of which is concerned the commodity export share model and the second model is concerned with the export concentration index, while the third model deals with the export diversity index. Based on the results of the conducted tests, namely; stabilization, homogeneity and joint integration tests, the variables were stable at the first, difference and homogenization tests showed heterogeneity in the three models, the joint integration test is between the absence of long relationship between the independent variables and the dependent variable in the three models. Consequently, the LSDV method was assessed and the results had a negative correlation between carbon emissions and the share of commodity exports, and concentration , diversity indicators, while there was a positive relationship between GDP and concentration and diversity indicators, and there was a negative correlation between the free trade index and export share and the concentration and diversification index, and there is correlation between the natural resources depletion index and the share of commodity exports, and a negative relationship between them and the index of concentration and diversity.
أطروحة دكتوراه تخصص دراسات كمية في التجارة الدولية في العلوم الاقتصادية وعلم التسيير
Keywords: الكلمات المفتاحية: معايير البيئية، صادرات السلعية، تنافسية الصادرات السلعية، بيانات البانل، طريقة المربعات الصغرى الوهمية(LSDV).; environmental standards, commodity exports, competitive commodity exports